Acute type A aortic dissection in patients with non-prior cardiac surgery vs. prior cardiac surgery: a systematic review and meta-analysis - Ahmed, Muhammad; Alim Ur Rahman, Hafsah; Fahim, Muhammad Ahmed Ali; Hussain, Zahabia Altaf; Ahmed, Nisar; Asghar, Muhammad Sohaib (Frontiers in Cardiovascular Medicine, 2024)
Background: Patients with prior cardiac surgery undergoing acute type A aortic dissection (ATAAD) are thought to have worse clinical outcomes as compared to the patients without prior cardiac surgery. Aim: To compare the safety and efficacy of ATAAD in patients with prior cardiac surgery. Methods: We systematically searched PubMed, Cochrane Library and Google Scholar from database inception until April 2024. We included nine studies which consisted of a population of 524 in the prior surgery group and 5,249 in the non-prior surgery group. Our primary outcome was mortality. Secondary outcomes included reoperation for bleeding, myocardial infarction, stroke, renal failure, sternal wound infection, cardiopulmonary bypass (CPB) time, cross-clamp time, hospital stay, and ICU stay. Results: Our pooled estimate shows a significantly lower rate of mortality in the non-prior cardiac surgery group compared to the prior cardiac surgery group (RR= 0.60, 95% CI= 0.48 to 0.74). Among the secondary outcomes, the rate of reoperation for bleeding was significantly lower in the non-prior cardiac surgery group (RR= 0.66, 95% CI= 0.50 to 0.88). Additionally, the nonprior cardiac surgery group had significantly shorter CPB time (MD= -31.06, 95% CI= -52.20 to -9.93) and cross-clamp time . All other secondary outcomes were statistically insignificant. Conclusion; Patients with prior cardiac surgery have a higher mortality rate as compared to patients who have not undergone cardiac surgery previously. Patients with prior cardiac surgery have higher mortality and longer CPB and cross-clamp times. Tailored strategies are needed to improve outcomes in this high-risk group.